Проектирование многозондовых устройств для тестирования электронных компонентов с шариковыми выводами - Невлюдов, И.Ш.; Палагин, В.А.; Разумов-Фризюк, Е.А.; Жарикова, И.В. (Технология и конструирование в электронной аппаратуре, 2016)
В продолжение работ авторов по проектированию многозондового подключающего устройства для контроля изделий с матричными шариковыми выводами, представлены новые результаты исследований опытного образца устройства. Предложено изменить форму зонда для снижения трудоемкости проектирования МПУ. Разработана коммутационная плата с ZIP-разъемами для подключения МПУ к автоматизированному измерительному устройству. В продовження робіт авторів з проектування багатозондового підмикального пристрою (БПП) для контролю виробів з матричними кульковими виводами, представлено нові результати досліджень експерементального зразка пристрою. Запропоновано змінити форму зонда для зниження трудомісткості проектування БПП. Розроблено комутаційну плату з ZIP-роз'ємами для підключення БПП до автоматизованого вимірювального пристрою. In the article design and technological features of multiprobe connecting device for testing the electronic components with matrix ball leads are described and substantiated. Such test fixture has probes made as two separated flatcontact lands that can be used for testing BGA/CSP components or microelectromechanical devices. Only in case, when two parts of probe contact lands are pressed to according lead of electronic component, electrical circuit between them closes. This fact confirms presence of contact between testing fixture probe and tested lead of BGA device and can be considered as way of testing reliability increasing. Due to the proposed new form of contact probe for electronic component testing it became possible to simplify the topology of connecting circuit board. Developed commutative board with ZIF connectors allows realizing multiprobe device connection to automated measuring systems, providing also the possibility of its future application to test other electronic components with more leads. Also the results of experimental and modeling research of developed device prototype are presented and explained. Obtained results substantiate the basic requirements for the multiprobe connecting device that should be observed during its contacting to the unit under test. Designed test fixture is more simple and cheap in comparison with its analogues. Also developed method of testing effectively provides the necessary contact pressure between test fixture and unit under test without hazard of its deformation which can appear in similar devices.